Security challenges in the transition to 4G mobile systems in developing countries. Issue 1 (31st December 2023) - Asmare, Fanuel Melak; Ayalew, Lijaddis Getnet
Abstract: 4 G mobile networks have evolved to meet the ever-increasing demand and requirements of users. 4 G will provide comprehensive IP solutions, allowing users to access voice, data, and streaming multimedia services at any time, from any location. Nonetheless, this transition will introduce new vulnerabilities and threats to service providers and customers. With the introduction of machine-to-machine (M2M) communication and the Internet of Things (IoT), malicious actors now have more attack ground. Attackers have an easier time sneaking into 4 G networks in developing countries because outdated and unprotected devices are still in use. Many startups and individuals did not invest in protecting their devices, owing to financial constraints and a lack of fundamental cyber security awareness. Because many network devices in developing countries are old and poorly protected, they could serve as a launching pad for perpetrators. This work thoroughly investigates and discusses fundamental security flaws in the 4 G network. These flaws could provide a path for malicious actors. Several factors exist in developing countries that expose them to perpetrators have been explained and elaborated on this work. Additionally, potential solutions to combat these issues are proposed.